Changing food nitrogen flow in a food-exporting city - Huang, Wei; Zhong, Qiumeng; Lu, Yang; Huang, Yunfeng; Cui, Shenghui; Gao, Bing (Frontiers in Sustainable Food Systems, 2023)
Nitrogen (N) plays a significant role in food systems, but only a fraction of N is effectively utilized and the rest is lost to the environment and negatively affects the ecosystem. So far, there has been relatively little research on N flow associated with the food production and consumption of production-oriented cities in developing countries. In this study, we present a comprehensive analysis of N flow in the food production and consumption system of Changchun in China between 1991 and 2014, and define three types of nitrogen use efficiency (NUE) and compare them. The results show that: (1)Total new N input into the food system in Changchun increased by 63.75% (240.8 to 394.3 Gg N yr-1) during the study period, mainly attributable to the high volume of food exports(total output from 47.63 to 72.51 Gg N yr-1). (2) Changchun typically exhibited lower apparent NUE and virtual NUE of the food system, while its actual NUE was typically higher, compared to food-importing cities. (3) The consumption of crop food witnessed a decrease from 24.2 Gg N in 1991 to 18.7 Gg N in 2014, whereas the consumption of animal food showed an upward trend from 2.5 Gg N to 7.7 Gg N. Both urban and rural residents consumed less grain food but more fruits and meat. (4) The total N loss has increased from 131.3 Gg N in 1991 to 266.6 Gg N in 2014.The crop production caused 58.1% of the total N loss in 2014, and the atmospheric loss accounted for 40.2% of the total. The study has revealed the distinctive features, fluctuations, and underlying drivers of N flow in the food-exporting city, setting it apart from food-importing city. These findings provide a valuable point of reference for the implementation of customized and diversified nitrogen management strategies in these specific urban areas.